COMPARATIVE ANALYSIS IN THE PERFORMANCE OF STUDENTS IN CHEMISTRY - Lacambra-Malana, Matilde (International Journal of Psychosocial Rehabilitation, 2020)
Chemistry is a subject that is usually found difficult by students, along with physics and some other areas of science. Aside from these, they find it not interesting and not useful. This study dealt about the difficulties of students in understanding Chemistry as a subject. It also dealt with finding out the difference in their cognitive performance when students are grouped according to select profile variables. The respondents in this study, 244 students participated and they come from both public and private High Schools in Cagayan. This study is descriptive and used the person product correlation technique. Data were gathered using an adapted questionnaire. Results revealed that most of the students find difficulty in answering higher order questions which resulted to their low cognitive performance in Chemistry. Their performance is also not affected by their profile. The researcher recommends that teachers may apply the difficult concepts and skills of cognition to achieve better learning process. If necessary, teachers may also give remedial teaching to poor learners in Chemistry.